Neoadjuvant Pembrolizumab and Chemotherapy in Resectable Esophageal Cancer: An Open-Label, Single-Arm Study (PEN-ICE) - Duan, Hongtao; Shao, Changjian; Pan, Minghong; Liu, Honggang; Dong, Xiaoping; Zhang, Yong; Tong, Liping; Feng, Yingtong; Wang, Yuanyuan; Wang, Lu; Newman, Neil B.; Sarkaria, Inderpal S.; et al. (Frontiers in Immunology, 2022)
Background In this single-arm study, the efficacy and safety of neoadjuvant pembrolizumab plus chemotherapy were evaluated in patients with resectable esophageal squamous cell carcinoma (ESCC). Methods This study included patients with ESCC of clinical stages II–IVA who underwent surgery within 4 to 6 weeks after completing treatment with pembrolizumab (200 mg) combined with a conventional chemotherapy regimen (3 cycles). The safety and efficacy of this combination treatment were evaluated as primary endpoints of the study. Results From April 2019 to August 2020, a total of 18 patients (including 14 men) were enrolled, of whom 13 patients progressed to surgery. Postoperative pathology revealed a major pathological response (MPR) in 9 cases (9/13, 69.2%) and a pathological complete response (pCR) in 6 cases (6/13, 46.2%). Five patients (5/18, 27.8%) experienced serious treatment-related adverse events (AEs) of grades 3–4. At the time of data cutoff (Mar 25, 2022), the shortest duration of follow-up was 17.8 months. Programmed death-ligand 1 (PD-L1) expression in pretreatment specimens was not significantly associated with the percentage of residual viable tumor (RVT) (r=−0.55, P=0.08). Changes in counts of CD68+ macrophage between pre- and post-treatment specimens were weakly correlated with RVT (r=0.71; P=0.07), while a positive correlation was observed between postoperative forkhead box P3-positive (Foxp3)+T cells/CD4+Tcells ratios and RVT (r=0.84, P=0.03). Conclusions The combination of neoadjuvant immunotherapy and chemotherapy for ESCC is associated with a high pathological response and immunologic effects in the tumor microenvironment (TME). It has acceptable toxicity and great efficacy, suggesting a strong rationale for its further evaluation in randomized clinical trials (RCTs). Trial Registration ChiCTR2100048917.